Obesity: a preventable risk factor for large joint osteoarthritis which may act through biomechanical factors. Issue 1 (23rd December 2004) - Powell, A; Teichtahl, A J; Wluka, A E; Cicuttini, F M
Abstract : Osteoarthritis (OA) is a common degenerative disease of joints. The major clinical features are pain and stiffness, leading to a decline in physical function, which may ultimately require joint replacement surgery. As no cure exists, current medical intervention focuses on symptomatic relief. Moreover, as no cure is imminent, preventable risk factors for the onset and progression of the disease are of great interest. Obesity is the main preventable risk factor that has been identified. Given that obesity is modifiable by conservative treatment such as weight loss, its potential importance in reducing the incidence of OA cannot be underestimated.